2003
DOI: 10.1002/eji.200324084
|View full text |Cite
|
Sign up to set email alerts
|

Preferential contribution of B7‐H1 to programmed death‐1‐mediated regulation of hapten‐specific allergic inflammatory responses

Abstract: Programmed death-1 (PD-1) and its ligands, B7-H1/PD-L1 and B7-DC/PD-L2, are new CD28-B7 family members that may be involved in the regulation of immune responses. We examined the roles of these molecules in mouse hapten-induced contact hypersensitivity (CH). Administration of anti-PD-1 mAb at sensitization significantly enhanced and prolonged ear swelling. Treatment with anti-B7-H1 mAb, but not anti-B7-DC mAb, also enhanced CH reactions. The anti-PD-1 mAb treatment at sensitization significantly increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 42 publications
9
92
0
Order By: Relevance
“…In doing so, we demonstrated that PD-1 ligation had no costimulatory activity and was very efficient in preventing suboptimal CD3/28 costimulation from inducing T cell proliferation and cytokine production. These data add to the growing body of evidence that direct ligation of PD-1 inhibits T cell activation (43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 51%
“…In doing so, we demonstrated that PD-1 ligation had no costimulatory activity and was very efficient in preventing suboptimal CD3/28 costimulation from inducing T cell proliferation and cytokine production. These data add to the growing body of evidence that direct ligation of PD-1 inhibits T cell activation (43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 51%
“…PMA was purchased from Sigma-Aldrich, and ionomycin and PP2 from EMD. Anti-mPD-L1 (MIH5) was previously described (Tsushima et al, 2003). B cell hybridomas producing anti-mCD3 (145-2C11) and anti-mCTLA-4 (UC10.4F10.11) were provided by J. Bluestone (University of California, San Francisco, CA); anti-mCD28 (PV-1) by R. Abe (Science University of Tokyo, Tokyo, Japan); anti-mTCR- (H57-597) by R.T. Kubo (Cytel Corp., San Diego, CA); anti-H-2K b (20-8-4) by N. Shinohara (Kitasato University, Tokyo, Japan); and anti-I-E k (14-4-4), antimCD80 (16-10A1), anti-mICAM-1 (YN1/1.7.4), and anti-I-E k in complex with MCC88-103 (D4; Reay et al, 2000) by M.L.…”
Section: Reagentsmentioning
confidence: 99%
“…Neutralizing mAbs against mouse PD-1 (RPMI-14), PD-L1 (MIH6), and PD-L2 (TY25) for in vivo experiments were prepared as described previously (10,14,27). Neutralizing mAbs against mouse PD-1 (RMPI-14) and PD-L2 (TY25) were kindly provided by Dr. H. Yagita, and a neutralizing mAb against mouse PD-L1 (MIH6) was kindly provided by Dr. M. Azuma.…”
Section: Administration Of Abs and Am80mentioning
confidence: 99%
“…1D, 1E) showed that Th17/Th1 cell expansion was detected during chronic GVHD and contributed to chronic GVHD progression (27). We next assessed Th subsets from pLNs of WT and PD-L1 2/2 recipients.…”
Section: Lack Of Pd-l1 Expression Exacerbated Chronic Gvhd With Il-17mentioning
confidence: 99%